A hybrid actuator with hollowed multi-drum magnetorheological brake and direct-current micromotor for hysteresis compensation. (April 2019) - Qin, Huanhuan; Song, Aiguo; Mo, Yiting
Based on magnetorheological fluid, magnetorheological brake can exhibit promising characteristics in haptics such as intrinsic passiveness and high torque density. The main difficulty in applying magnetorheological brake lies in the magnetic hysteresis. To deal with the magnetic hysteresis, a magnetorheological brake was combined with a micromotor to construct a hybrid actuator in this article. A novel hollowed multi-drum architecture was adopted for the brake so that the micromotor could be placed inside the brake to obtain a compact structure. The brake produced the maximum torque of 1263.39 mN m with 40 mm diameter and 28 mm length. Through the closed-loop control, no obvious hysteresis loop was observed in the hybrid actuator current–torque figure. The maximum difference between the forward and backward torque was reduced from 7.2% to 1.94% of the total torque range. The dynamic range was increased from 41.17 to 45.42 dB. Furthermore, the experimental results proved that the hybrid actuator could track the reference signals more accurately than the brake.